Quantifying capital goods for waste landfilling. Issue 6 (June 2013) - Brogaard, Line K; Stentsøe, Steen; Willumsen, Hans Christian; Christensen, Thomas H
Materials and energy used for construction of a hill-type landfill of 4 million m 3 were quantified in detail. The landfill is engineered with a liner and leachate collections system, as well as a gas collection and control system. Gravel and clay were the most common materials used, amounting to approximately 260 kg per tonne of waste landfilled. The environmental burdens from the extraction and manufacturing of the materials used in the landfill, as well as from the construction of the landfill, were modelled as potential environmental impacts. For example, the potential impact on global warming was 2.5 kg carbon dioxide (CO2 ) equivalents or 0.32 milli person equivalents per tonne of waste. The potential impacts from the use of materials and construction of the landfill are low-to-insignificant compared with data reported in the literature on impact potentials of landfills in operation. The construction of the landfill is only a significant contributor to the impact of resource depletion owing to the high use of gravel and steel.